Lacto-fermented polypeptides integrated with edible coatings for mango mangifera indica L. bio-preservation - Ranjith, Fernando H.; Muhialdin, Belal J.; Arroo, Randolph; Yusof, Noor Liyana; Mohammed, Nameer K.; Meor Hussin, Anis Shobirin (Elsevier, 2021)
Mango (Mangifera indica L.) is one of the most important tropical fruits due to its pleasant taste and high nutrient content including vitamins, minerals, and phytochemicals. Post-harvest fungal diseases, mainly anthracnose, stem-end rot, and aspergillus rot are among the major problems in mango provision throughout all the supply chain stages. Fungal diseases create large economic losses and present a health risk for consumers due to the production of mycotoxins (aflatoxin and patulin). In the last two decades, chemical methods for fungal control have been prevalent because of their low cost and simple practicing features. However, recent consumer trends and regulations have limited the use of chemicals in fruits at the post-harvest stage. Bio-preservation is a promising alternative technique applied to control the post-harvest fungi with high safety for the consumer and environment. Antifungal polypeptides are made by different living beings including bacteria, fungi, protozoa, plants, invertebrates, and vertebrates. Polypeptides including small peptides produced by lactic acid bacteria (LAB) have a higher potential to employ as food bio-preservatives due to their promising antifungal ability with generally recognized as safe (GRAS) status. Lacto-fermented polypeptides inhibit a broad range of fungal growth, and thus enhance the quality and extend the shelf life through reducing biotic stress, respiration, and ethylene biosynthesis of post-harvested fruits. Recently, polypeptides, mainly bioactive peptides, and bacteriocins received great attention for their potential bio-preservation activity against pathogenic fungi in fruits. Moreover, the development of edible coating enhanced the stability of the bioactive polypeptides and expanded their applications for fruit preservation. This article reviews the fungi associated with main mango diseases, major causal organisms, antifungal activity of LABs’ polypeptides on mango, and their antifungal performances to control the postharvest mango spoilage. Besides, this review highlights the potential applications of Lacto-fermented polypeptides-enriched edible coating to control the pathogenic fungi of mango.